Atrial natriuretic peptide attenuates the development of pulmonary hypertension in rats adapted to chronic hypoxia. - Jin, H (1990)
To test the hypothesis that chronic infusion of atrial natriuretic peptide (ANP) instituted before hypoxic exposure attenuates the development of pulmonary hypertension in hypoxia adapted rats, ANP (0.2 and 1.0 microgram/h) or vehicle was administered intravenously via osmotic minipump for 4 wk beginning before exposure to 10% O2 or to room air. Low dose ANP increased plasma ANP levels by only 60% of vehicle controls after 4 wk and significantly decreased mean pulmonary arterial pressure (MPAP) (P less than 0.01), the ratio of right ventricular weight to body weight (RV/BW) (P less than 0.01), and the wall thickness of small (50-100 microns) pulmonary arteries (P = 0.01) in hypoxia-adapted rats. ANP did not alter any of these parameters in air-control rats. High dose ANP increased plasma ANP levels by 230% of control and produced greater reductions in MPAP (P less than 0.001) and RV/BW) (P less than 0.05), but not in pulmonary arterial wall thickness, than the low dose. Neither dose of ANP altered mean systemic arterial pressure in either hypoxic or normoxic rats. The data demonstrate that chronic infusion of exogenous ANP at a dose that does not affect MPAP or RV weight in air-control rats attenuates the development of pulmonary hypertension and RV enlargement in rats adapted to chronic hypoxia.